2020
DOI: 10.3857/roj.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of coplanar and non-coplanar volumetric-modulated arc therapy in head and neck cancer treated with radiotherapy

Abstract: Head and neck cancers form about 30% of the total malignancies registered in a year in India. More than 400,000 new cases are diagnosed per annum [1,2]. Radiotherapy plays a major role in the management of this diverse spectrum of malignancies in the definitive, adjuvant and palliative setting. The major proportion of patients in India present in the advanced stages of the disease which further cements the position of radiotherapy in the plan of management. In the radical scheme of treatment of head and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…For higher dose (i.e., more proximal) structures such as the mandible and larynx, the average maximum dose differences were around 2 Gy, i.e., less than 50 cGy per fraction. This is consistent with the report by Gayen et al, who showed that the low dose spillage volume of V5Gy was marginally increased with non-coplanar VMAT, although V10Gy was reduced [40].…”
Section: Discussionsupporting
confidence: 93%
“…For higher dose (i.e., more proximal) structures such as the mandible and larynx, the average maximum dose differences were around 2 Gy, i.e., less than 50 cGy per fraction. This is consistent with the report by Gayen et al, who showed that the low dose spillage volume of V5Gy was marginally increased with non-coplanar VMAT, although V10Gy was reduced [40].…”
Section: Discussionsupporting
confidence: 93%
“…In Section 3.3, it was shown that there is a positive correlation between the target volumes and the number of noncoplanar arcs, corroborating this trend. Therefore, it should not be concluded that the V10Gy, V12Gy, and V14Gy would be larger when using noncoplanar arcs, because in our department, noncoplanar arcs are used when coplanar arcs do not achieve good results, as well as recent studies suggest that noncoplanar arcs can achieve better planning results 17‐21 …”
Section: Resultsmentioning
confidence: 86%
“…Therefore, it should not be concluded that the V10Gy, V12Gy, and V14Gy would be larger when using noncoplanar arcs, because in our department, noncoplanar arcs are used when coplanar arcs do not achieve good results, as well as recent studies suggest that noncoplanar arcs can achieve better planning results. 17 , 18 , 19 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…The scatter contribution from the collimator and patient body along with softer energy spectrum outside the treatment field (compared with within the treatment field) plays a vital role in the irradiation dose to normal tissues outside the target volume [25,26]. Moreover, Fig.…”
Section: Discussionmentioning
confidence: 99%